Robot-Assisted in Hip and Knee Surgery: Are we ready? - Sholahuddin Rhatomy,MD; Krisna Yuarno Phatama; Asep Santoso; Kukuh Dwiputra Hernugrahanto; Nicolaas Budhiparama (The Hip and Knee Journal, 2021)
The word 'robot' is derived from the Polish word "robota," which means forced labor. It describes a machine that carries out various tasks either automatically or with minimal external input, especially one that is programmable. There are two main types of robotic surgery systems: haptic and autonomous. Haptic or tactile systems allow the surgeon to use or drive the robot to perform a surgical procedure. This technology requires constant input by the surgeon for the procedure to proceed. In contrast, autonomous robotic systems require the surgeon to perform the approach and set up the machine, but once engaged, the robot completes the surgery without the surgeon's help. The use of robotic technology has, in some cases, facilitated minimally invasive surgery, which has gained popularity with some patients. In spinal surgery, robotic technology has been successfully used to increase the accuracy of implant placement. Furthermore, robotic technology can improve the radiological alignment of implants following the pre-operative plan.1,2